PERAN DAN METODE PENDAMPINGAN REMAJA KATOLIK DI PAROKI SANTA MARIA JOMBANG - Dato, Sopiana; Ardijanto, Don Bosco Karnan (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2019)
This research aims to explore the roles and mentoring methods of Catholic adolescent facilitators in the Santa Maria Jombang Parish. Utilizing a qualitative methodology, the study involved purposive sampling to select informants, comprising both facilitators and adolescents. Data collection was conducted through voice call interviews. The findings reveal four key conclusions: first, the facilitators are recognized as adults who play a vital role in nurturing and accompanying Catholic adolescents, embodying their vocation and mission; second, a variety of mentoring methods are employed by the facilitators; third, adolescents perceive that their facilitators align with their expectations due to their personalities and spirituality; and fourth, there are specific mentoring methods that adolescents prefer or dislike. This study highlights the importance of effective mentorship in the spiritual development of Catholic youth.